TYPOGRAPHY ON DESIGN T SHIRT SUPORTER OF PERSIB - Muhammad Hidayatulloh; Iman Somargono (Balong International Journal of Design, 2018)
AbstractAs  a  type  of  clothing  used  in  daily  life,  a  t  shirt  at  this  time often displays  images  and  text  on  the   surface.  Picture  or  text  in  a  t  shirt,  can act  as  aesthetic  element  or  a  form  of  expression  as  well  as   identity  for the wearer.  For  the  supporters  of  Persib,  t  shirt  becomes  one  of  the  attributes that  they   often  use  in  supporting  Persib  both  in  the  field  and  off  the  field. T  Shirt  of  the  supporters,  generally   uses  text  elements  as  part  of  the design  elements  and  conveys  messages  to  support  Persib.  Text  on  t   shirt supporters  of  Persib,  is  packed  in  such  a  way  to  attract  the  attention  of the audience.  In  the   perspective  of  typography,  the  letters  in  the  text  not  only play  a  role  in  preparing  a  textual  message   but  also  it  can  present  a  visual perception  that  is  able  to  support  the  message  containing  and  attract   the attention  of  the  audience.Keywords:  t  shirt,  supporter,  persib,  typography